Women elite Italian football players' perceptions on gender equality and dual career opportunities - Guidotti, Flavia; Ciaccioni, Simone; Demarie, Sabrina; Colombo, Piersanto; López De Subijana, Cristina; Padua, Elvira; Capranica, Laura (Frontiers in Sports and Active Living, 2025)
IntroductionThe aim of the present study was to explore dual career experiences of elite women Italian football players in light of potential gender inequalities that might have affected their sporting and academic career paths.MethodsA 25-items semi-structured questionnaire was administered to 22 elite Italian football players (age: 25.8 ± 4.3 years).ResultsThe mixed-method thematic analysis highlighted participants' difficulties in combining sport and education (e.g., lack of time, lack of dual career opportunities), reporting a higher support received from the sporting context (e.g., training absences and schedule adaptation) rather than from the educational institutions (e.g., lack of flexibility for class absences and for exams/evaluation schedule). Seven participants only benefited from the recognition of the “student-athlete status” and the formal access to a dual career program, mainly due to gender differences in the recognition of eligible competitive levels and past gender equality policies. Furthermore, the gender pay gap in professional football was perceived as a crucial factor in determining women's major interest in academics and educational achievements over their football performance development.DiscussionThe present findings reflect previous literature in this field, with the football career perceived as unsecure and precarious, even more for women in such male-dominated industry, urging them to prioritize their education. Although the recent professional recognition was positively perceived, the present study highlighted the need for further research in this area. Furthermore, the translation of evidence-based information into further policy implementation towards gender mainstreaming and equal dual career paths in football should be envisioned.